PATHOMORPHOLOGICAL SIGNS OF EXPERIMENTAL THYROTOXICOSIS OF THE ADRENAL AND TESTIS GLANDS - Aziz S. Ilyasov,; Baxtiyor S. Umarkulov,; Gulbahor A. Umarkulova, (Central Asian Journal of Medicine, 2023)
The adrenal glands and testis of intact rats and animals that received a single dose of levothyroxine through a probe do not differ significantly in weight. With a 14-day administration of levothyroxine, the morphometric parameters of the adrenal glands and testis of rats are significantly different from those of intact animals. Thus, in the control group, the proliferative index in the cortical layer of the adrenal glands was above 10%, and in the cerebral layer 7-9%. When exposed to levothyroxine sodium in the experimental group, the proliferative index in the cortical layer decreased to 5%, and in the cerebral layer below 1%. Significant changes were also observed in testicular tissue, notably in the experimental group the seminiferous tubes were found to be smaller and smaller to medium in size compared to the control group and the basal membrane thinned. In addition, there is a significant disorganization of the spermatogenic epithelium, and 60% of the ducts are emptied. In small quantities, only spermatogonium and sperm are visible. There are calcinates in the epithelial layer of some twisted tubes, intermediate sex cells were not observed in these tubules.